2018
DOI: 10.1016/j.freeradbiomed.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative cross-linking of proteins to DNA following ischemia-reperfusion injury

Abstract: Myocardial infarction (MI) is a life-threatening condition that can occur when blood flow to the heart is interrupted due to a blockage in one or more of the coronary vessels. Current treatments of MI rapidly restore blood flow to the affected myocardium using thrombolytic agents or angioplasty. Adverse effects including inflammation, tissue necrosis, and ventricular dysfunction are, however, not uncommon following reperfusion therapy. These conditions are thought to be caused by a sudden influx of reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Furthermore, reoxygenation can cause oxidative damage via a surge of reactive oxygen species (ROS) from the mitochondrial electron transport system (ETS) (Andrienko et al, 2017;Jastroch et al, 2010). Oxidative stress is considered a hallmark of the hypoxiareoxygenation (H-R) injury in hypoxia-sensitive organisms such as terrestrial mammals and, if left unchecked, leads to the accumulation of cellular damage and eventually cell death (Cadenas, 2018;Groehler et al, 2018;Ham and Raju, 2016;Hernansanz-Agustín et al, 2014). Studies in hypoxia-tolerant animals, such as freshwater turtles, crucian carp, and intertidal mollusks and fish, uncovered several putative mitochondrial mechanisms that can mitigate oxidative stress during H-R.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, reoxygenation can cause oxidative damage via a surge of reactive oxygen species (ROS) from the mitochondrial electron transport system (ETS) (Andrienko et al, 2017;Jastroch et al, 2010). Oxidative stress is considered a hallmark of the hypoxiareoxygenation (H-R) injury in hypoxia-sensitive organisms such as terrestrial mammals and, if left unchecked, leads to the accumulation of cellular damage and eventually cell death (Cadenas, 2018;Groehler et al, 2018;Ham and Raju, 2016;Hernansanz-Agustín et al, 2014). Studies in hypoxia-tolerant animals, such as freshwater turtles, crucian carp, and intertidal mollusks and fish, uncovered several putative mitochondrial mechanisms that can mitigate oxidative stress during H-R.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is another well-known process after myocardial I/R injury, leading to death of cardiomyocytes. In our study, we assessed oxidative stress and inflammatory factors after ROSC, and established that oxidative stress and inflammation were involved in myocardial dysfunction, as other studies have similarly shown [11][12][13].…”
Section: Discussionmentioning
confidence: 82%
“…ROS, which is released during the I/R process, promotes tissue inflammation, and activates immune responses through NLRP3 inflammasome, inducing the secretion of pro-inflammatory cytokine Interleukin 1β(IL-1β) and cell pyroptosis [ 10 ]. Recent studies showed that NAC suppressed cardiomyocytes pyroptosis by inhibiting ROS in a myocardial infarction model [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute hypoxia was found to induce oxidative stress due to the excessive reactive oxygen species (ROS) production in P. vannamei [79,80]. Oxidative damage due to the excessive ROS production is considered a major contributor to oxidative injury during hypoxia-reoxygenation stress [81][82][83]. Glutathione is an antioxidant that effectively scavenges free radicals such as ROS and reactive nitrogen species (RNS) (e.g., hydroxyl radical, hydrogen peroxide, lipid peroxyl radical and superoxide anion) directly and indirectly through the glutathione cycle [84].…”
Section: Discussionmentioning
confidence: 99%